Penerapan senam egrenomik terhadap tekanan darah pada lansia yang mengalami hipertensi - Wulan, Sarinah Sri; Khomsah, Ida Yatun (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Ikatan Dokter Indonesia (IDI), 2024)
Background: Hypertension occurs when blood pressure is more than 140/90 mmHg. Hypertension is a condition in which there is an abnormal and continuous increase in blood pressure on several blood pressure checks caused by one or more risk factors that do not work properly in maintaining normal blood pressure. Treatment of hypertension can be done from pharmacology and non-pharmacology, one of which is egrenomic exercise. Egrenomic Gymnastics is a method that is practical, effective, efficient, and logical in maintaining the health of the human body. Egrenomic exercises are able to restore and improve the position and flexibility of the nervous system and blood flow, maximizing the supply of oxygen to the brain. Purpose: To obtain an overview of the application of egrenomic exercise to blood pressure in the elderly with hypertension. Method: A descriptive using a case study approach. The subjects in this scientific paper are two elderly patients with hypertension. Results: It can lower blood pressure after the application of agronomic gymnastics. There was a decrease in blood pressure in subject I on the first day from 160/100 mmHg, on the fifth day from 140/80 mmHg, in subject II from 150/100 mmHg, on the fifth day from 130/80 mmHg. Conclusion: There are changes in blood pressure in elderly people with hypertension before and after doing agronomic exercises. Keywords: Egrenomic Gymnastics; Elderly; Hypertension Literature Pendahuluan: Hipertensi terjadi jika tekanan darah lebih dari 140/90 mmHg. Hipertensi adalah suatu keadaan dimana terjadi peningkatan tekanan darah secara abnormal dan terus-menerus pada beberapa kali pemeriksaan tekanan darah yang disebabkan satu atau beberapa factor risiko yang tidak berjalan sebagaimana mestinya dalam mempertahankan tekanan darah secara normal. Pengobatan hipertensi dapat dilakukan dari farmakologi maupun non farmakologi salah satunya yaitu dengan senam egrenomik. Senam Egrenomik adalah suatu metode yang praktis, efektif, efisien, dan logis dalam memelihara kesehatan tubuh manusia. Senam Egrenomik mampu mengembalikan dan memperbaiki posisi dan kelenturan sistem saraf dan aliran darah, memaksimalkan suplai oksigen ke otak. Tujuan: Untuk memperoleh gambaran penerapan senam egrenomik terhadap tekanan darah pada lansia yang mengalami hipertensi. Metode: Deskriptif dengan menggunakan pendekatan studi kasus. Subyek yang digunakan adalah dua orang pasien lansia yang mengalami hipertensi. Hasil: Dapat menurunkan tekanan darah sesudah dilakukan penerapan senam egrenomik. Terjadi penurunan tekanan darah pada subjek I hari pertama 160/100 mmHg hari ke lima 140/80 mmHg, subjek II 150/100 mmHg hari ke lima 130/80 mmHg. Simpulan: Terdapat perubahan tekanan darah pada lansia dengan hipertensi sebelum dan sesudah dilakukan senam egrenomik. Kata Kunci: Hipertensi; Lansia; Senam Egrenomik.